(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
In this article, the essence of efficiency in service enterprises, its socio-economic content, the system of indicators that represent it, the principle of calculating productivity and efficiency indicators, the approach of resource consumption and goal orientation in calculating efficiency, and their interdependence are researched